2011
DOI: 10.1097/aog.0b013e3182342b7f
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Maternal Sex Steroids During the First Half of Pregnancy

Abstract: Objective To examine the associations of maternal and child characteristics with early pregnancy maternal concentrations of testosterone, androstenedione, progesterone, 17-hydroxyprogesterone and estradiol. Methods We analyzed these hormones among 1,343 women with singleton pregnancies who donated serum samples to the Finnish Maternity Cohort from 1986 to 2006 during the first half of pregnancy (median, 11 weeks). The associations of maternal and child characteristics with hormone concentrations were investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
103
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(117 citation statements)
references
References 41 publications
11
103
2
1
Order By: Relevance
“…He interpreted this as a sign that T can transfer, at least from the fetus to the mother. However, several other studies failed to find a difference in maternal T levels by the sex of the fetus (Glass and Klein, 1981;Rodeck et al, 1985;van de Beek et al, 2004;Cohen-Bendahan et al, 2005b;Toriola et al, 2011). In fact, studies that measured T in both amniotic fluid and maternal serum found no correlation between the two measures (Rodeck et al, 1985;van de Beek et al, 2004).…”
Section: Testosterone Transfermentioning
confidence: 90%
“…He interpreted this as a sign that T can transfer, at least from the fetus to the mother. However, several other studies failed to find a difference in maternal T levels by the sex of the fetus (Glass and Klein, 1981;Rodeck et al, 1985;van de Beek et al, 2004;Cohen-Bendahan et al, 2005b;Toriola et al, 2011). In fact, studies that measured T in both amniotic fluid and maternal serum found no correlation between the two measures (Rodeck et al, 1985;van de Beek et al, 2004).…”
Section: Testosterone Transfermentioning
confidence: 90%
“…[38][39][40][41] Furthermore, differences in maternal metabolic and hormonal environment between nulliparous and multiparous women may influence fetoplacental development. [41][42][43] Impaired fetal growth, followed by infant catch-up growth, may influence risks of adiposity and adverse cardiometabolic outcomes in later life. 7,44 Animal studies also suggested an increase in fat mass and alterations in endocrine sensitivity in adipose tissue in firstborn offspring, which may also be important risk factors for obesity and related disorders in later life.…”
Section: Biological Mechanismsmentioning
confidence: 99%
“…Smoking is known to impact the metabolism of multiple sex steroids. In a study by Toriola et al, 16 for example, smoking was noted to reduce levels of progesterone while actually increasing levels of 17 α-hydroxyprogesterone. It is possible that smokers treated with 17OHP-C may thus be both relatively progesterone deficient and have relatively augmented levels of 17OHP-C.…”
Section: Commentmentioning
confidence: 95%
“…Smoking has been reported to alter the metabolism of progestogens, possibly rendering pregnant smokers relatively progestogen deficient. 16 17OHP-C is postulated to achieve its benefits via anti-inflammatory mechanisms, 17,18 and one pathway by which smoking is thought to increase PTB is via inflammation. 8 Manuck et al have published pharmacogenomic data suggesting that 17OHP-C effectiveness may be linked to nitric oxide metabolism, 9 which is adversely impacted by smoking.…”
mentioning
confidence: 99%